2018
DOI: 10.1002/mnfr.201800086
|View full text |Cite
|
Sign up to set email alerts
|

Piperine Promotes Glucose Uptake through ROS‐Dependent Activation of the CAMKK/AMPK Signaling Pathway in Skeletal Muscle

Abstract: Piperine in pepper prevents hyperglycemia by GLUT4 translocation through CaMKKβ/AMPK signaling via TRPV1-dependent increase in the intracellular Ca level and ROS generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 46 publications
1
29
1
Order By: Relevance
“…In addition, recent research findings showed evidence that suggests the ability of some alkaloids to mediate in the insulin‐signal transduction pathway, reverse molecular defects resulting in insulin resistance and glucose intolerance, and improve disease complications, in vitro and in vivo (Christodoulou et al, 2019). In this context, piperine promotes glucose uptake in skeletal muscles via ROS‐dependent activation of CAMMK/AMPK signaling pathway (Maeda et al, 2018). Treatment of diabetic rats with piperine caused a significant decrease in the concentration of blood sugar and increased insulin secretion (Kaur et al, 2016).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…In addition, recent research findings showed evidence that suggests the ability of some alkaloids to mediate in the insulin‐signal transduction pathway, reverse molecular defects resulting in insulin resistance and glucose intolerance, and improve disease complications, in vitro and in vivo (Christodoulou et al, 2019). In this context, piperine promotes glucose uptake in skeletal muscles via ROS‐dependent activation of CAMMK/AMPK signaling pathway (Maeda et al, 2018). Treatment of diabetic rats with piperine caused a significant decrease in the concentration of blood sugar and increased insulin secretion (Kaur et al, 2016).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Piperine activates PPARγ, leading to inhibition of AKT/GSK3β and reduction of cardiac fibrosis [105]. As piperine phosphorylates AMP-activated protein kinase, facilitates glucose transporter 4 to enter the plasma membrane, increase the intracellular Ca2+ level and activation of Ca2+/calmodulin-dependent protein kinase kinase-beta, it also possesses hyperglycemia-preventing effect [106]. Piperine may act as a novel therapeutic agent for melanoma, as it increases the ratio of Bax and Bcl-2, upregulates the expression of apoptosis-inducing factor, and reduces UVB-induced p-glycoprotein activity in B16F10 mouse melanoma cells [73].…”
Section: Miscellaneous Activity-kinase Inflammation Diabetesmentioning
confidence: 99%
“…One member of this class in particular—CaMKK2—is able to phosphorylate Thr172 and may be activated by increase of Ca 2+ and ROS concentrations inside the cell [ 25 , 26 ]. It is found that presence of the piperine—an alkaloid widely present in food, can contribute to an increase of Ca 2+ and ROS concentrations inside the cell, hence activation of CaMKKβ [ 5 ].…”
Section: Structure and Activation Of Ampkmentioning
confidence: 99%
“…Reduced sensitivity to insulin and impaired glucose uptake leads to an increased level of total blood glucose. Since IR primarily affects skeletal muscle, liver and adipose tissue, it has a significant impact on energy-consuming metabolic pathways [1,3,5]. Many of existing biochemical pathways involved in human energy generation and consumption are proved to be modulated by AMPK (AMP-activated protein kinase)-key molecular target in treatment of metabolic syndrome and related abnormalities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%